2022
DOI: 10.1186/s12957-022-02552-y
|View full text |Cite
|
Sign up to set email alerts
|

Survival and prognostic factors in patients undergoing pulmonary metastasectomy for lung metastases from retroperitoneal sarcoma

Abstract: Background Soft-tissue sarcomas are rare malignancies that consist of many different histologic subtypes and arise in various locations in the body. In patients with lung metastases from retroperitoneal sarcomas, the long-term outcomes and prognostic factors are unknown. This study is a retrospective review of patients undergoing pulmonary metastasectomy for retroperitoneal sarcoma metastases at one institution, with the purpose of determining prognostic factors and clinical outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Previous studies have reported that age, histological grading, pathological subtype, multifocality, and R0 resection are the main prognostic factors affecting DMFS following surgical resection in patients with RLS [ 14 , 30 , 31 ]. However, in the present study, the clinical model constructed based on the semantic imaging features identified as independent predictors of MDM in the univariate and multivariate analyses (tumor size > 10 cm) had an AUC of 0.511.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that age, histological grading, pathological subtype, multifocality, and R0 resection are the main prognostic factors affecting DMFS following surgical resection in patients with RLS [ 14 , 30 , 31 ]. However, in the present study, the clinical model constructed based on the semantic imaging features identified as independent predictors of MDM in the univariate and multivariate analyses (tumor size > 10 cm) had an AUC of 0.511.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, studies on retroperitoneal primary tumors are focused more on adult patients [7][8][9][10][11] than pediatric patients, resulting in insufficient evidence for the pediatric retroperitoneal non-organ-originated malignancies. [12][13][14] Moreover, due to limited incidences and a small number of cases included in most studies, it is difficult to systematically summarize the clinicopathological features, treatment, prognosis, and prognostic analysis of pediatric patients with retroperitoneal tumors.…”
Section: Introductionmentioning
confidence: 99%